2020
DOI: 10.1103/physrevresearch.2.013269
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical formation of quantum droplets in a K39 mixture

Abstract: We report on the dynamical formation of self-bound quantum droplets in attractive mixtures of 39 K atoms. Considering the experimental observations of Semeghini et al., Phys. Rev. Lett. 120, 235301 (2018), we perform numerical simulations to understand the relevant processes involved in the formation of a metastable droplet from an out-of-equilibrium mixture. We first analyze the so-called self-evaporation mechanism, where the droplet dissipates energy by releasing atoms, and then we consider the effects of l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 20 publications
6
37
0
Order By: Relevance
“…This behavior was then confirmed by the theoretical analysis reported in Ref. [28], where the complex dynamics taking place during the droplet formation is thoroughly described. There, it was shown that the evolution of the system is indeed dominated by the presence of three-body losses and by a continuous release of atoms to restore the proper population ratio, whereas the self-evaporation mechanism plays only a negligible role, if any.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…This behavior was then confirmed by the theoretical analysis reported in Ref. [28], where the complex dynamics taking place during the droplet formation is thoroughly described. There, it was shown that the evolution of the system is indeed dominated by the presence of three-body losses and by a continuous release of atoms to restore the proper population ratio, whereas the self-evaporation mechanism plays only a negligible role, if any.…”
Section: Introductionsupporting
confidence: 76%
“…Once the initial state is prepared, the optical dipole trap is switched off and the system is let to evolve. The droplet dynamics is studied here by solving the following set of GP equations [13,28,34,35]…”
Section: Dynamicsmentioning
confidence: 99%
“…3). Small values imply that losses play an important role in the droplet dynamics [16]. We find that it is indeed fa-vorable to move toward δa > 0 in order to minimize the relative effect of losses.…”
Section: Quantum Droplets In the Bulkmentioning
confidence: 74%
“…Experimentally, the droplets are observed at high densities (typically ∼ 10 21 m −3 ). Three-body losses thus play an important role in the droplet dynamics [16] and have hindered the observation of the predicted characteristic flat-top density profile of a stable droplet.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, we plan to increase this time by slowing down the droplet's fall, thanks to a species-dependent optical potential [15]. The experimental realization of long-lived droplets opens up the possibility of studying their peculiar properties, such as their excitation spectra [24,38] and the predicted self-evaporation [24,43].…”
Section: Discussionmentioning
confidence: 99%